Refining of Mackerel Fish Oil from Fish Meal Processing Byproduct with Alkali Neutralization - I Wayan Kukuh Feryana; Sugeng Heri Suseno; Nurjanah - - (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2014)
Fish oil neutralization with alkali was a common refining technique used to separate impurities and decrease oil oxidation parameters value. The purpose of this study were to analyze oxidation parameters and determine the best NaOH concentration treatment. The best NaOH concentration to neutralize mackerel fishmeal processing byproduct (Scomber japonicus) oil was 24oBe (17.87% NaOH) with 56.33±1.15% yield; peroxide value (PV) 5.60±0.42 meq/kg; p-Anisidine value (AnV) 14.31±0.15 meq/kg; percentage of free fatty acid (%FFA) 2.16±0.25%; acid value (AV) 4.30±0.49 mg KOH/kg and total oxidation value (TOTOX) 25.53±0.71 meq/kg.Keywords: fish oil, mackerel, neutralization